The Interrelationship Between Emotional Intelligence, Self-Efficacy, and Burnout Among Foreign Language Teachers: A Meta-Analytic Review - Wang, Yabing; Wang, Yangyu (Frontiers in Psychology, 2022)
The importance of teachers’ affective, cognitive, and motivational factors in students’ academic achievement and well-being has been widely acknowledged. These factors are of great relevance, especially in the foreign language learning context wherein interaction between teachers and students is frequent and varies in forms. Though abundant evidence points to the high prevalence and risky factors of burnout among such a group, the extant literature lacks a quantitative synthesis of the interrelationship between emotional intelligence (EI), self-efficacy (SE), and burnout among them. This study aims to fill this research gap. The current meta-analysis is based on 42 independent samples with the experiences of 5,665 teachers reviewed. Results demonstrated moderate to large meta-correlations between these three constructs in the expected directions. EI and SE are positively correlated with each other, but negatively correlated with burnout. Moderation analysis also provides exploratory insights into the effects. Implications and future directions are also discussed.